Recent Advances and Opportunities in the Study of Candida albicans Polymicrobial Biofilms - Pohl, Carolina H. (Frontiers in Cellular and Infection Microbiology, 2022)
It is well known that the opportunistic pathogenic yeast, Candida albicans, can form polymicrobial biofilms with a variety of bacteria, both in vitro and in vivo, and that these polymicrobial biofilms can impact the course and management of disease. Although specific interactions are often described as either synergistic or antagonistic, this may be an oversimplification. Polymicrobial biofilms are complex two-way interacting communities, regulated by inter-domain (inter-kingdom) signaling and various molecular mechanisms. This review article will highlight advances over the last six years (2016-2021) regarding the unique biology of polymicrobial biofilms formed by C. albicans and bacteria, including regulation of their formation. In addition, some of the consequences of these interactions, such as the influence of co-existence on antimicrobial susceptibility and virulence, will be discussed. Since the aim of this knowledge is to inform possible alternative treatment options, recent studies on the discovery of novel anti-biofilm compounds will also be included. Throughout, an attempt will be made to identify ongoing challenges in this area.